AN ANALYSIS OF STUDENTS' DIFFICULTIES IN WRITING RECOUNT TEXT IN ELEVENTH GRADE OF SMA N 1 BAE KUDUS ACADEMIC YEAR 2022/2023 - Aini, Mawarina Nurul; Syafei, Muh; Nurcahyo, Agung Dwi (SIMPLE: International Journal of English Education, 2023)
Teaching English in Senior High School significantly emphasizes enhancing four fundamental language skills: listening, speaking, reading, and writing. The objective is for students to attain mastery of all four language skills. Among these, the enhancement of productive skills, particularly writing, holds paramount importance in English instruction. Nonetheless, in practical application, numerous students encounter challenges when it comes to composing English texts. Therefore, this research aims to analyze students’ difficulties in writing recount text at eleventh students SMA N 1 Bae Kudus. The research design of this study is content analysis qualitative research. The researcher analyzed the students’ recount texts based on the writing aspect that should be considered by the students in writing a recount text which is content, organization, grammar, vocabulary, and mechanics. It was found that students' difficulties in writing recount text were in five categories: content (21,3%), organization (19,4%), vocabulary (19,7%), language use (18,5%), and mechanic (21,1%). Furthermore, it can be concluded that the difficulty in writing recount text by students of class XI IPA 4 and XI IPA 7 SMA N 1 BAE Kudus academic year 2022/2023 is in the Language Use section with the lowest score 984 (18,5%).